Reversible Functional Changes Evoked by Anodal Epidural Direct Current Electrical Stimulation of the Rat Auditory Cortex - Colmenárez-Raga, Ana Cecilia; Díaz, Iván; Pernia, Marianny; Pérez-González, David; Delgado-García, José M.; Carro, Juan; Plaza, Ignacio; Merchán, Miguel A. (Frontiers in Neuroscience, 2019)
Rat auditory cortex was subjected to 0.1 mA anodal direct current in seven 10-min sessions on alternate days. Based on the well-known auditory cortex control of olivocochlear regulation through corticofugal projections, auditory brainstem responses (ABRs) were recorded as an indirect test of the effectiveness and reversibility of the multisession protocol of epidural stimulation. Increases of 20–30 dB ABR auditory thresholds shown after epidural stimulation reverted back to control levels 10 min after a single session. However, increases in thresholds revert 4 days after multisession stimulation. Less changes in wave amplitudes and threshold shifts were shown in ABR recorded contralaterally to the electrically stimulated side of the brain. To assess tissue effects of epidural electric stimulation on the brain cortex, well characterized functional anatomical markers of glial cells (GFAP/astrocytes and Iba1/microglial cells) and neurons (c-Fos) were analyzed in alternate serial sections by quantitative immunocytochemistry. Restricted astroglial and microglial reactivity was observed within the cytoarchitectural limits of the auditory cortex. However, interstitial GFAP overstaining was also observed in the ventricular surface and around blood vessels, thus supporting a potential global electrolytic stimulation of the brain. These results correlate with extensive changes in the distribution of c-Fos immunoreactive neurons among layers along sensory cortices after multisession stimulation. Quantitative immunocytochemical analysis supported this idea by showing a significant increase in the number of positive neurons in supragranular layers and a decrease in layer 6 with no quantitative changes detected in layer 5. Our data indicate that epidural stimulation of the auditory cortex induces a reversible decrease in hearing sensitivity due to local, restricted epidural stimulation. A global plastic response of the sensory cortices, also reported here, may be related to electrolytic effects of electric currents.